Case for diagnosis - Joanna Pimenta de Araujo Franco; Caroline Cruz Barbosa; Bárbara Ferreira Saraiva da Fonseca; Ricardo Barbosa Lima; Antônio Macedo D'Acri; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2014)
Dermatofibrosarcoma protuberans is a fibrohistiocytic tumor of intermediate malignancy with aggressive localized growth, high recurrence rate, but low metastatic potential. It appears as a hardened plaque, with slow growth, upon which the development of nodules occurs. It predominates in the trunk and is unusual in acral locations. Histopathology reveals spindle cells with storiform pattern and cartwheel-like or whirlwind-like aspect. Immunohistochemistry shows positivity for CD34. The treatment is surgical. We report a case of long evolution, with an unusual location, that relapsed after surgery, to emphasize the importance of early diagnosis and proper treatment, avoiding aggressive resections with increased morbidity.